2016
DOI: 10.1002/ijc.30115
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, weight gain, and ovarian cancer risk in African American women

Abstract: Although there is growing evidence that higher adiposity increases ovarian cancer risk, little is known about its impact in African American (AA) women, the racial/ethnic group with the highest prevalence of obesity. We evaluated the impact of body mass index (BMI) 1 year before diagnosis and weight gain since age 18 years on ovarian cancer risk in a population-based case-control study in AA women in 11 geographical areas in the US. Cases (n = 492) and age and site matched controls (n = 696) were identified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 40 publications
0
22
0
1
Order By: Relevance
“…Overall, these data suggest that insulin is an important extracellular signal that could modulate DHCR24 expression via STAT3 to promote cell metastasis and progestin resistance in EC. Hyperinsulinemia in insulin resistance is one of the proposed mechanisms that explains the obesity-cancer link and has a detrimental effect on survival in cancer73132. Understanding the insulin signaling pathway involved in cell metastasis and progestin resistance will be critical for the development of new intervention strategies to prevent or treat EC associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these data suggest that insulin is an important extracellular signal that could modulate DHCR24 expression via STAT3 to promote cell metastasis and progestin resistance in EC. Hyperinsulinemia in insulin resistance is one of the proposed mechanisms that explains the obesity-cancer link and has a detrimental effect on survival in cancer73132. Understanding the insulin signaling pathway involved in cell metastasis and progestin resistance will be critical for the development of new intervention strategies to prevent or treat EC associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…African American women and Hispanic women have been shown to have a higher rate of obesity and have a higher body mass index (BMI) 18. A large prospective study demonstrated that the risk of death from ovarian cancer was higher in women with a BMI of 35–40 kg/m 2 when compared with those with a BMI of 18.5–24.9 kg/m 2 19 20. We thought this would correlate with Hispanic women having poorer outcomes; however, this study shows that instead they had shorter length of stay and a lower number of ‘deceased’ status at last contact.…”
Section: Discussionmentioning
confidence: 68%
“…Übergewicht und Fettleibigkeit erhöhen das Risiko für das Auftreten eines Ovarialkarzinoms [20,21,43,[46][47][48]…”
Section: Antihormontherapie Als Medikamentöse Präventive Maßnahmeunclassified